Higher education on agroforestry: My experience as a agroforestry graduate - M.S., Syamili (Indian Journal of Agroforestry, 2022)
In this era of the climate crisis, agroforestry is a popular land-use strategy and agroforestry education is pertinent. Here is a personal assessment of agroforestry education in the United Kingdom and India. Due to the subject’s dynamic nature, agroforestry education should take a multifaceted approach. Instead of focusing exclusively on the agroforestry practices prevalent, it should also address the pressing problems for which it offers a solution. Students should be aware of the political and social ramifications of the subject in addition to the science behind it. This will prepare students to critically evaluate what they learned as well as exposed to various perspectives of the field